A case-crossover study of transient risk factors for occupational acute hand injury. Issue 4 (18th March 2004) - Sorock, G S; Lombardi, D A; Hauser, R; Eisen, E A; Herrick, R F; Mittleman, M A
Abstract : Background: Workers with acute hand injuries account for over 1 000 000 emergency department visits annually in the United States. Aims: To determine potential transient risk factors for occupational acute hand injury. Methods: Subjects were recruited from 23 occupational health clinics in five northeastern states in the USA. In a telephone interview, subjects were asked to report the occurrence of seven potential risk factors within a 90-minute time period before an acute hand injury. Each case also provided control information on exposures during the month before the injury. The self-matched feature of the study design controlled for stable between-person confounders. Results: A total of 1166 subjects were interviewed (891 men, 275 women), with a mean age (SD) of 37.2 years (11.4). The median time interval between injury and interview was 1.3 days. Sixty three per cent of subjects had a laceration. The relative risk of a hand injury was increased when working with equipment, tools, or work pieces not performing as expected (11.0, 95% CI 9.4 to 12.8), or when using a different work method to do a task (10.5, 95% CI 8.7 to 12.7). Other transient factors in decreasing order of relative risk were doing an unusual task, being distracted, and being rushed. Wearing gloves reduced the relative risk by 60% (0.4, 95% CI 0.3 to 0.5). Occupational category, job experience, and safety training were found to alter several of these effects. Conclusion: The results suggest the importance of these transient, potentially modifiable factors in the aetiology of acute hand injury at work. Attempts to modify these exposures by various strategies may reduce the incidence of acute hand injury at work.